Challenges and opportunities in managerial agility-based moderation at the Religious Education and Training Center, Makassar - Hanafi Pelu; Amir Imbaruddin; Wahyu Nurdiansyah N; Andi Rasdiyanti (CV. Literasi Indonesia, 2026)
This research aims to investigate the challenges and opportunities inherent in implementing managerial agility-based moderation at the Makassar Religious Education and Training Center. As public sector organizations navigate increasingly complex and dynamic environments, the integration of agile methodologies within traditional bureaucratic structures has become a critical focal point for administrative reform. The primary objective of this study is to identify the specific factors that hinder or facilitate the adoption of managerial agility in promoting religious moderation and institutional effectiveness. Employing a qualitative research approach, the study utilizes an ethnographic design to gain in-depth insights into the organizational culture and individual experiences of key institutional actors. Data were collected through semi-structured interviews with diverse informants, supplemented by document reviews and participant observations to ensure comprehensive triangulation. The findings reveal that the primary challenges are rooted in psychological resistance, deeply ingrained rigid mindsets, and the heterogeneity of participants' prior understanding of agile concepts. Conversely, the implementation offers significant opportunities for enhancing strategic decision-making, fostering collaborative networks, and creating a more responsive organizational ecosystem. Ultimately, this research underscores that while the transition is energy-intensive and requires a paradigm shift, managerial agility serves as a vital competency for sustaining innovation and service quality within the Ministry of Religious Affairs. These results provide a practical roadmap for institutional leaders to balance modern administrative efficiency with established ethical and religious foundations.